El lago pleistoceno de soatá (boyacá, colombia): consideraciones estratigráficas, paleontológicas y paleoecológicas (2001)
The detailed study of the sedimentites cropping out at the upper heads of the Portugalete and Ovachia creeks, SSE and NNE of Soatá respectively, allow to establish the presence of a lake (Lake of Soatá) , which was a result of the damming of the ancestor of the Chicamocha river downstream of the School of Jútua. Two age dating based on C14 (45.900± 1.600 and 39.600± 800 years BP) have been able to determine that the lake was formed in the Middle Pleni-Glacial Age, probably during the interstadial of Chicagota of the Middle Fuquean. The sediments studied as a new litostratigraphic unit -Soatá Formation- suggest that the environmental conditions were hot and dry with serious variations in the rainy regime. Additionally, the knowledge of the fossil mammals (Haplomastodon waringi, Odocoileus cf. salinae and Neochoerus sp.), collected in the Soatá Formation, is more accurate and considerably increased as well as the identification of some gastropods.